Study the Reproductive Pattern of Different Breeds Bitches in Iraq by estimation of Kisspeptin and detection ovulation time. - Sulake Fadhil Abbas Al-Zubaidi; Souhayla O. Hussain (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study was conducted to investigate the reproductive pattern of bitches by estimation the optimumtime of ovulation and kisspeptin level. The study included 245 bitches (different breeds), from March/2019to the end of February/2020.Canine ovulation timing kits was applied in order to determine the ovulationtime. For estimation of Kisspeptin, blood collection of 80 samples allocated approximately 7 samples foreach monthby using ELISA kit. The resultsrevealed the time of ovulation ranged from 2 to 5 days after thebeginning of the estrus phase.The results showed that concentration of kisspeptin during different phases ofthe estrous cycle was (257.01±11.08, 262.93±9.15, 227.98±14.91 and 244.89±11.99) pg/mL for Proestrus,Estrus, Diestrus, and Anestrus respectively with no significant (p>0.05) differences among different estrouscycle phase. The concentration of kisspeptin in which distributed according to the season showed that itwas (218.26±11.92, 254.12±10.09, 246.00±10.22, and 287.11±9.00) pg/ml for Spring, Summer, Autumn,and Winter, respectively and there was a significant difference (p<0.05) between Summer and Winter. Asa conclusion, the ovulation timing kit was accurate and useful for detecting the time of ovulation and theseason had a significant effect on the kisspeptin level.